Hepatotoxicity after Sevoflurane Exposure in a Patient with Chronic Hepatitis C - Shah, Nickul N; Ballone, Nina; Zamora, Raul; DeVito, Peter; Wilson, Samuel (Global Journal of Medical and Clinical Case Reports, 2015)
<span style="color: #222222; font-family: Roboto, serif; font-size: 15px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Sevoflurane is considered a safe inhaled anesthetic of choice in patients with liver disease. Compared to other halogenated inhaled anesthetics, Sevoflurane is reported to lessen the severity of decreased hepatic blood flow and undergoes a different mechanism of hepatic metabolism. In patients with preexisting liver disease, there is potential for low-flow Sevoflurane to induce acute liver damage through other mechanisms. Limited data exists to guide clinical decision-making when quantifying the severity of cirrhosis in patients with hepatitis C and its relationship to anesthesia choice. Previous studies have found that exposure to general anesthesia during abdominal surgery may increase the risk of hepatorenal failure. This study has raised a concern that anesthetics may interfere with various hepatic functions secondary to viral infection. The generation of abnormal liver enzymes and hypercoagulation has provided further exploration for such toxicity.